2023
DOI: 10.3390/ani13101587
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Pets in the United Arab Emirates as Reservoirs for Antibiotic-Resistant Bacteria: A Comprehensive Analysis of Extended-Spectrum Beta-Lactamase Producing Escherichia coli Prevalence and Risk Factors

Abstract: Extended-spectrum β-lactamases resistant (ESBL-R) Escherichia coli (E. coli) has been reported from healthy and sick pets. However, data from Middle Eastern countries, including the United Arab Emirates (UAE), are minimal. This study provides the first evidence of ESBL-R E. coli carriage among pets in the UAE. A total of 148 rectal swabs were collected from domestic cats (n = 122) and dogs (n = 26) attending five animal clinics in the UAE. Samples were cultured directly onto selective agar, and suspected colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…These results agree with those reported in other studies carried out in Europe, with the results from Italy being the most similar to those of the present study [30]. Other authors have also reported the highest AMR to this antibiotic, ranging from 40 to almost 100% in different studies worldwide, regardless of whether they were studies carried out in asymptomatic [47][48][49][50] or symptomatic [43,44,[51][52][53][54] dogs and cats. Moreover, these results have also been found in food-producing animals [17] and humans [51,55], which highlights the global impact of this issue.…”
Section: Discussionsupporting
confidence: 93%
“…These results agree with those reported in other studies carried out in Europe, with the results from Italy being the most similar to those of the present study [30]. Other authors have also reported the highest AMR to this antibiotic, ranging from 40 to almost 100% in different studies worldwide, regardless of whether they were studies carried out in asymptomatic [47][48][49][50] or symptomatic [43,44,[51][52][53][54] dogs and cats. Moreover, these results have also been found in food-producing animals [17] and humans [51,55], which highlights the global impact of this issue.…”
Section: Discussionsupporting
confidence: 93%
“…Knowing these rates could potentially be used to parameterize epidemiological models to predict the impact of interventions to reduce the burden of ARB gene carrying E coli. One possible explanation for the high similarity and transmission of the ABR-E. coli in humans and canines is a cohabitation between the two species such as canine ownership, which has been shown to contribute to E. coli sharing and long-term colonization (66), ( 64), (67). Alternatively, it is also possible the fecal samples originated from canines unrelated to the human samples such as passersby's walking their canines or strays.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, EIEC is the causative agent of the invasive, dysenteric form of diarrhea because of its ability to invade the colonic mucosa. EHEC produces Vero or Shiga toxins and is the causative agent of hemorrhagic colitis and bloody diarrhea [25,26].…”
Section: Introductionmentioning
confidence: 99%